Keterpaduan Antara Beternak Puyuh, Lele Dan Azolla Dalam Mengatasi Limbah Puyuh Dan Mahalnya Pakan Lele - Sudadi Sudadi (PRIMA: Journal of Community Empowering and Services, 2017)
This IbM program in collaboration with two partners, namely: (1) Breeders quail "Panjer Rino", and (2) Livestock Catfish "Dwipangga". Partner (1) is located in the hamlet of Gunung Sari, Ngringo village, district. Cork, Kab. Karanganyar, with a distance of about ± 3.5 km from Fak. Agriculture UNS. The problem faced by business partners (1) is the production of livestock waste quail (quail droppings) are very high, which is about 200 kg of waste per day (6 tons per month). Currently, the waste dumped directly into nearby rivers, contaminating the river water. Dirt quail very high in protein (17-21%). Natural nature catfish food is dirt ("telek"). The problem faced by partners (2) is a high cost to provide quality catfish feed. Catfish feed requirement per week reached 200-250 kg, with an average feed price Rp. 8.300, - per kg. Therefore we need an alternative feed supply, such as pellets of excrement quail that can be produced using animal manure quail. Azolla is the only genus of floating water fern. It can be used as green manure, Azolla is used to feed the fish because they contain high nutritional and floats that can be eaten fish or made pellets. The purpose of this activity is to address the key problems: Partner (1) ie quail livestock waste treatment technology that can be used to manufacture pellets. Partners (2) that address the high cost of feed catfish feed Azolla can use directly and make pellets of Azolla and dirt quail. The method used in this activity is to give guidance to partners and practice on: the use of quail dung to feed catfish; the practice of making pellets using quail dung mixed Azolla, Azolla maintain direct practice in catfish ponds and catfish farming. Outcomes that will result from the planned activities IbM are: pellets of excrement quail and Azolla for catfish feed and Azolla as catfish feed directly.